CTEVT Toward Skills Enhancement in Nepal - Neupane, Rabindra Kumar; Timilsina, Jagat (DEPAN, 2024)
This article highlights the role of CTEVT for skill enhancement in Nepal. Therefore, the objective of this article is to evaluate the role of CTEVT in producing technical and vocational manpower in different professions by examining its achievements in organizing skills training, institutional partnership building, and number of skilled human resources produced. Data has been collected from secondary sources i.e. published annual progress reports and journals of CTEVT and other associated partners. The collected data have been examined, summarized, and interpreted by adopting a descriptive research design. This study has identified that CTEVT has progressively developed complete mechanisms for skill enhancement through arrangements of technical and vocational training programs, institutional strengthening through partnership development, identification of current and future market skill needs in collaboration with industries and academia, development of innovative curriculums, and production of qualified professionals via skill tests programs. Therefore, it is concluded that CTEVT has played a vital role in the production of skilled workers and professionals based on current as well as future market needs in Nepal. The findings of this article will be very beneficial to industry owners, un-employed youths, semi as well as self-employed personnel, and interested private and community skill training institutions.